A review of the techniques for the mold manufacturing of micro/nanostructures for precision glass molding. (19th July 2021) - Zhou, Tianfeng; He, Yupeng; Wang, Tianxing; Zhu, Zhanchen; Xu, Ruzhen; Yu, Qian; Zhao, Bin; Zhao, Wenxiang; Liu, Peng; Wang, Xibin
Abstract: Micro/nanostructured components play an important role in micro-optics and optical engineering, tribology and surface engineering, and biological and biomedical engineering, among other fields. Precision glass molding technology is the most efficient method of manufacturing micro/nanostructured glass components, the premise of which is meld manufacturing with complementary micro/nanostructures. Numerous mold manufacturing methods have been developed to fabricate extremely small and high-quality micro/nanostructures to satisfy the demands of functional micro/nanostructured glass components for various applications. Moreover, the service performance of the mold should also be carefully considered. This paper reviews a variety of technologies for manufacturing micro/nanostructured molds. The authors begin with an introduction of the extreme requirements of mold materials. The following section provides a detailed survey of the existing micro/nanostructured mold manufacturing techniques and their corresponding mold materials, including nonmechanical and mechanical methods. This paper concludes with a detailed discussion of the authors recent research on nickel-phosphorus (Ni-P) mold manufacturing and its service performance.